'Double Capture' and De-Democratisation: Interest Group Politics and Uganda's 'Transport Mafia'. Issue 10 (3rd October 2017) - Goodfellow, Tom
Abstract: This article analyses problems of interest representation and democratic consolidation, using a case study of the Uganda Taxi Operators and Drivers Association (UTODA). It shows how apparently representative organisational forms can exploit the majority of their members, bolstering the power of political-economic elites who straddle the state-society divide, as well as how such organisations can undermine the foundations for democratic consolidation more broadly. Challenging conventional understandings of 'state capture', the paper argues that UTODA's organisational power instead evolved through processes conceptualised as 'double capture': first, the government infiltrated the informal transport sector, but subsequently the transport organisation came to wield disproportionate influence over the state itself, with detrimental effects on both urban services and popular representation. The long-term domination by this authoritarian organisation meant that even after its downfall in 2011 there was little organisational capacity to build on in the sector, facilitating the reassertion of top-down governmental control.